2018
DOI: 10.21037/atm.2018.03.27
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer genomics and designing rational trials

Abstract: The widespread use of next generation sequencing (NGS) has led to a refined understanding of the genomics of colorectal cancer (CRC). However, progress in the use of molecular biomarkers in standard practice has been slow, and there is no approved targeted therapy for CRC based on a positive predictive marker yet. In this review, we will first summarize biomarkers with clinical utility in standard practice or targeted therapy trials and then consider how to rationally design clinical trials to more effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“…Cases were associated with ODC1 genotype considered as cancer risk (CC) or protective (CT/TT) based on the colon cancer literature using a chi-square analysis (p = 0.021). (44)(45)(46) In the unadjusted logistic regression model, the ODC1 SNP was associated with GC (OR=1.21, 95% CI 1.14, 1.80; p=0.027). In the model adjusted for age, sex, and CagA status, and FDR corrected for multiple testing, the ODC1 SNP was significantly associated with GC (OR = 1.36, 95% CI 1.05, 1.76; p=0.018) (Table 2, Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Cases were associated with ODC1 genotype considered as cancer risk (CC) or protective (CT/TT) based on the colon cancer literature using a chi-square analysis (p = 0.021). (44)(45)(46) In the unadjusted logistic regression model, the ODC1 SNP was associated with GC (OR=1.21, 95% CI 1.14, 1.80; p=0.027). In the model adjusted for age, sex, and CagA status, and FDR corrected for multiple testing, the ODC1 SNP was significantly associated with GC (OR = 1.36, 95% CI 1.05, 1.76; p=0.018) (Table 2, Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…The median survival for V600E BRAF (the most common BRAF mutation) patients with unresectable mCRC has been reported to be as low as less than 12 months . In fact, this poor prognosis seems to be unchanged despite the introduction of modern combination chemotherapies, and may be explained by the distinct pattern of metastatic spread . Specifically, these patients are more likely to have widespread extrahepatic metastases and in particular peritoneal metastases, which are associated with poor survival.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have shown that the pathogenesis of tumors has a complex molecular mechanism including activation of proto-oncogenes, inactivation and loss of tumor suppressor genes, and disorders in apoptosis-regulating genes and DNA repair genes (16)(17)(18)(19). Tumorigenesis is a multi-step process.…”
Section: Discussionmentioning
confidence: 99%